2001
DOI: 10.1159/000054942
|View full text |Cite
|
Sign up to set email alerts
|

EEG Source Localization and Global Dimensional Complexity in High- and Low- Hypnotizable Subjects: A Pilot Study

Abstract: Individuals differ in hypnotizability. Information on hypnotizability-related EEG characteristics is controversial and incomplete, particularly on intracerebral source localization and EEG dimensionality. 19-channel, eyes-closed resting EEGs from right-handed, healthy, 8 high- and 4 low-hynotizable subjects (age: 26.7 ± 7.3 years) were analyzed. Hypnotizability was rated after the subjects’ ability to attain a deep hypnotic stage (amnesia). FFT Dipole Approximation analysis in seven EEG frequency bands showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 45 publications
5
16
0
3
Order By: Relevance
“…This is consistent with previous research indicating that highly suggestible individuals exhibit greater posterior upper alpha power (Williams & Gruzelier, 2001). Other complementary research has suggested that highly suggestible individuals exhibit reduced anterior connectivity in the beta band but increased posterior connectivity in the theta band following an induction (Jamieson & Burgess, 2014), which is in line with other resting state EEG findings (Isotani et al, 2001) and the observation of reduced frontal connectivity among highly suggestible individuals during a selective attention task following an induction (Egner et al, 2005). These and other results may be reconciled through a shift from an anterior to a posterior neurophysiological mode, as observed in patients with schizophrenia (Holt et al, 2011).…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitysupporting
confidence: 86%
“…This is consistent with previous research indicating that highly suggestible individuals exhibit greater posterior upper alpha power (Williams & Gruzelier, 2001). Other complementary research has suggested that highly suggestible individuals exhibit reduced anterior connectivity in the beta band but increased posterior connectivity in the theta band following an induction (Jamieson & Burgess, 2014), which is in line with other resting state EEG findings (Isotani et al, 2001) and the observation of reduced frontal connectivity among highly suggestible individuals during a selective attention task following an induction (Egner et al, 2005). These and other results may be reconciled through a shift from an anterior to a posterior neurophysiological mode, as observed in patients with schizophrenia (Holt et al, 2011).…”
Section: Neurocognitive Bases Of Hypnosis and Hypnotic Suggestibilitysupporting
confidence: 86%
“…High and low hypnotizables were also distinguished by means of changes in mismatch negativity across hypnosis and pre-and post-hypnosis conditions . Isotani et al (2001) made an important point: already before hypnosis was induced, high and low susceptible subjects were in different brain electric states. In high-hypnotizables posterior brain activations were most pronounced whereas lows presented with anterior weighted brain activation patterns.…”
Section: Hypnosismentioning
confidence: 99%
“…Por su parte, Isotani et al (2001) investigaron las fuentes de actividad EEG para varias bandas de frecuencia durante hipnosis neutral. Los resultados mostraron que la banda beta (12.5-30 Hz) y theta (6.5-8 Hz) presentaron una fuente más posterior en sujetos altamente hipnotizables que en bajamente hipnotizables.…”
Section: Correlatos Neurobiológicos Del Estado Hipnóticounclassified
“…La modulación de actividad tanto en la corteza cingulada anterior como en la corteza dorsolateral frontal ha sido vinculada con el control del estado consciente, regulación del self y de los contenidos de conciencia a través de mecanismos de atención ejecutiva (Rainville et al 2002). Por esta razón se plantea que la modulación en dichas regiones cerebrales podría, al menos en parte, dar cuenta de las alteraciones perceptuales espontáneas observadas durante la experiencia hipnótica neutral (Rainville et al 2002;McGeown et al 2009;Egner et al 2005;Gruzelier, 1996;Isotani et al 2001). Por su parte, la activación de la corteza occipital (Rainville et al 1999; y el aumento de la conectividad funcional entre esta región y la corteza inferotemporal (Fin-gelkurts et al 2007) han sido propuestas, en su conjunto, como un posible marcador del estado hipnótico que facilitaría la imaginería visual (Rainville et al 2002;Fingelkurts et al 2007).…”
Section: Hacia Una Anatomía Funcional Del Estado De Conciencia Hipnóticounclassified
See 1 more Smart Citation